Geolocalizing with LKT: Digital Teaching Competence and Space Competence with TPACK - Gómez-Trigueros, Isabel María (Revista de Estudios Andaluces, 2020)
Research on training in knowledge related to geolocation with technologies shows the training potentials and limitations that these resources offer for teachers in training. This study examines the perceptions of the instructional effectiveness of mobile devices and geolocation software, by analyzing the performance in the TPACK skills dimensions of future teachers (n = 383). A mixed methodology has been implemented, with a descriptive cross-sectional approach as well as inferential analysis based on questionnaires (α ≥ .903) and the tasks carried out by the sample. The results show a poor didactic use of technologies while confirming the acquisition of knowledge about geolocation. This corroborates the benefits of applying an improvement in the digital competence of teachers in training